2015
DOI: 10.14257/ijt.2015.3.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inertial choice behavior based expected and experienced savings from a real-world route choice experiment

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The study assumes that a certain percentage of travelers follow the recommended route and others decide to divert based on their congestion perception. To estimate this percentage, many studies have been conducted on drivers' behavioral response to traveler information systems (Bhavsar et al, 2007;Horowitz et al, 2003;Kattan et al, 2013;Khattak et al, 1993;Khattak et al, 1996;Peeta and Jeong, 2006;Vreeswijk et al, 2015). The drivers' response is a function of various factors such as trip characteristics, the number of available alternate routes, delay information, and duration (Khattak et al, 1993).…”
Section: Experiments Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study assumes that a certain percentage of travelers follow the recommended route and others decide to divert based on their congestion perception. To estimate this percentage, many studies have been conducted on drivers' behavioral response to traveler information systems (Bhavsar et al, 2007;Horowitz et al, 2003;Kattan et al, 2013;Khattak et al, 1993;Khattak et al, 1996;Peeta and Jeong, 2006;Vreeswijk et al, 2015). The drivers' response is a function of various factors such as trip characteristics, the number of available alternate routes, delay information, and duration (Khattak et al, 1993).…”
Section: Experiments Results and Analysismentioning
confidence: 99%
“…In addition, a certain percentage of drivers (α) who are unfamiliar with the area and not using GPS device are assumed to divert to the recommended alternate route, whereas the aforementioned others are assumed to divert based on the UE assignment. Many studies that have been conducted on drivers’ behavioral response to the traveler information systems are used to estimate the percentage of drivers (α) who are diverting (Bhavsar et al., ; Horowitz et al., ; Kattan et al., ; Khattak et al., ; Khattak et al., ; Peeta and Jeong, ; Vreeswijk et al., ). Moreover, the number of travelers truef̂ijgoing from origini, to destination j in the subnetwork Gis estimated in Section 2.3.1.…”
Section: Methodsmentioning
confidence: 99%
“…One potential explanation for such behavior is that individuals tend to minimize their (cognitive) efforts at the cost of the accuracy of their choice outcome according to some sort of effort-accuracy trade-off framework (Johnson and Payne 1985). In line with this, several studies found that travelers choose a short travel time alternative, although not necessarily the shortest travel time alternative (e.g., Ciscal-Terry et al 2016;Vreeswijk et al 2015;Zhu and Levinson 2010). These findings indicate that individuals do not necessarily want to use the route alternatives that benefit them the most, are not able to correctly identify these or are not particularly interested in this.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In line with this, several studies found that travellers choose a short travel time alternative, although not necessarily the shortest travel time alternative (e.g. Ciscal-Terry, Dell'Amico, Hadjidimitriou, & Lori, 2016;Vreeswijk, Rakha, Van Berkum, & Van Arem, 2015;Zhu & Levinson, 2010). These findings indicate that individuals do not necessarily want to use the route alternatives that benefit them the most, are not able to correctly identify these or are not particularly interested in this.…”
Section: Problem Statementmentioning
confidence: 85%
“…The concept of individual day-to-day route choice patterns was proposed by Tawfik et al (2010). They introduced four different choice patterns or so-called driver types, which were characterized by Vreeswijk et al (2015) as Stayers, Tryers, Explorers and Switchers. Our research explores if similar patterns can be identified in the context of real-world experiments and if certain patterns occurred more often in response to travel time information.…”
Section: Can Different Behavioural Patterns or Profiles Be Identifiedmentioning
confidence: 99%